An in silico, in vitro and in vivo investigation of indole-3-carboxaldehyde identified from the seawater bacterium Marinomonas sp. as an anti-biofilm agent against Vibrio cholerae O1. Issue 4 (20th April 2016) - Rajalaxmi, Murugan; Beema Shafreen, Rajamohamed; Iyer, Prasanth M.; Sahaya Vino, Raja; Balamurugan, Krishnaswamy; Pandian, Shunmugiah Karutha
Abstract: Biofilm formation is a major contributing factor in the pathogenesis of Vibrio cholerae O1 (VCO1) and therefore preventing biofilm formation could be an effective alternative strategy for controlling cholera. The present study was designed to explore seawater bacteria as a source of anti-biofilm agents against VCO1. Indole-3-carboxaldehyde (I3C) was identified as an active principle component in Marinomonas sp., which efficiently inhibited biofilm formation by VCO1 without any selection pressure. Furthermore, I3C applications also resulted in considerable collapsing of preformed pellicles. Real-time PCR studies revealed the down-regulation of virulence gene expression by modulation of the quorum-sensing pathway and enhancement of protease production, which was further confirmed by phenotypic assays. Furthermore, I3C increased the survival rate of Caenorhabditis elegans when infected with VCO1 by significantly reducing in vivo biofilm formation, which was corroborated by a survivability assay. Thus, this study revealed, for the first time, the potential of I3C as an anti-biofilm agent against VCO1.